Structure‐Switching RNAs: From Gene Expression Regulation to Small Molecule Detection. Issue 4 (25th January 2021) - Husser, Claire; Dentz, Natacha; Ryckelynck, Michael
Abstract : RNA is instrumental to cell life in many aspects, especially gene expression regulation. Among the various known regulatory RNAs, riboswitches are particularly interesting cis ‐acting molecules as they do not need cellular factor to achieve their function and are therefore highly portable from one organism to the other. These molecules usually found in the 5′ untranslated region of bacterial messenger RNAs are able to specifically sense a target ligand via an aptamer domain prior to transmitting this recognition event to an expression platform that turns on, or off, the expression of downstream genes. In addition to their obvious scientific interest, these modular molecules can also serve for the development of synthetic RNA devices with applications ranging from the control of transgene expression in gene therapy to the specific biosensing of small molecules. The engineering of such nanomachines is greatly facilitated by the proper understanding of their structure as well as the introduction of new technologies. Herein, a general overview of the current knowledge on natural riboswitches prior to explaining the main strategies used to develop new synthetic structure‐switching molecules (riboswitches or biosensors) controlled by small molecules is given. Abstract : Riboswitches are RNA modules found in bacterial messenger RNAs whom they regulate the fate in a stand‐alone manner depending on the presence of a target small molecule. These molecules are fascinating on a biological point of view, but they also have plenty of applications (e.g., transgene regulation or biosensing), both aspects are reviewed herein.